Photoelectron Spectroscopy and Structures of X−⋅⋅⋅CH2O (X=F, Cl, Br, I) Complexes. Issue 1 (1st December 2020) - Corkish, Timothy R.; Haakansson, Christian T.; Watson, Peter D.; McKinley, Allan J.; Wild, Duncan A.
Abstract: A combined experimental and theoretical approach has been used to investigate X − ⋅⋅⋅CH2 O (X=F, Cl, Br, I) complexes in the gas phase. Photoelectron spectroscopy, in tandem with time‐of‐flight mass spectrometry, has been used to determine electron binding energies for the Cl − ⋅⋅⋅CH2 O, Br − ⋅⋅⋅CH2 O, and I − ⋅⋅⋅CH2 O species. Additionally, high‐level CCSD(T) calculations found a C2v minimum for these three anion complexes, with predicted electron detachment energies in excellent agreement with the experimental photoelectron spectra. F − ⋅⋅⋅CH2 O was also studied theoretically, with a Cs hydrogen‐bonded complex found to be the global minimum. Calculations extended to neutral X⋅⋅⋅CH2 O complexes, with the results of potential interest to atmospheric CH2 O chemistry. Abstract : Noncovalent interactions : Gas‐phase complexes formed between halide anions and CH2 O have been studied experimentally through the pairing of mass spectrometry and photoelectron spectroscopy. CCSD(T) calculations have also been performed on these systems and are found to have excellent experimental agreement as well as the potential to be of atmospheric interest.